Prediction of age from both measurements and body weights in Khillar cattle - Pawar KK; Ulmek BR; Patil SR (Journal of Livestock Biodiversity, 2025)
The data on body measurement traits of 71 male and 83 female Khillar calves from birth to 30 months of age were recorded to study breed characteristics. The data were classified according to the age of animals in five age groups, viz. M1 (0-3), M2 (3-6), M3 (6-12). M4 (12-18) and M5 (18-30 months of age). The reliability of predictions of age from body measurements traits and body weight was high (>90 per cent) in male and female Khillar calves. The best-fit prediction equations were obtained at 18-30 months of age in male and female Khillar calves. The age of the calves could be satisfactorily predicted from body weight at 18-30 months of age in male and females.